Assurbanipal's Elamite Campaigns. A Literary and Political Study - Gerardi, Pamela D. (1987)
Dissertation; University Microfilms Order No. DA8714039. Supervisor: E. Leichty; additional members of the dissertation committee: B. Eichler and J. D. Muhly; Introduction. Sources: The Texts — The Reliefs and Associated Texts. The Elamite Campaigns of Asb. Conclusions